2016
DOI: 10.1590/0102-6720201600s10017
|View full text |Cite
|
Sign up to set email alerts
|

Pre- And Postoperative in Bariatric Surgery: Some Biochemical Changes

Abstract: Background:The bariatric surgery may cause some nutritional deficiencies. Aim: To compare the serum levels of biochemical markers, in iimmediate post-surgical patients who were submitted to bariatric surgery. Methods: Non-concurrent prospective cross-sectional study. The analysis investigated data in medical charts of pre-surgical and immediate post-surgical patients who were submitted to bariatric surgery, focusing total cholesterol, HDL cholesterol, LDL cholesterol, triglycerides, C reactive protein, vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Similarly, other reports have found a clear downward trend in BMI post-BS. [20] Our results showed successful weight loss (defined as ≥ 50% EWL) among participants over 1 year. At 6 months postoperatively, 56.8% of the participants successful EWL, and at 9 months, 83.3% had successful EWL.…”
Section: Discussionsupporting
confidence: 51%
“…Similarly, other reports have found a clear downward trend in BMI post-BS. [20] Our results showed successful weight loss (defined as ≥ 50% EWL) among participants over 1 year. At 6 months postoperatively, 56.8% of the participants successful EWL, and at 9 months, 83.3% had successful EWL.…”
Section: Discussionsupporting
confidence: 51%
“…However, a retrospective cohort study including 163 obese patients demonstrated the reduction in the metain ammation up to 4 years after the bariatric surgery by reporting complete normalization of hs-CRP in 84.0 % of patients in 4 years The intensity of weight loss was also reported to have a signi cant linear effect on change in WBC and change in hs-CRP at long term follow-up (16). Improvements in blood glucose and lipid pro le (TC, LDL-C and TG) is important to reduce major cardiovascular risk factors and it has been well documented in various studies within the 6 months after the surgical intervention (13,17). In our study, a signi cant decrease in TC, LDL and also VLDL has been achieved at the 6th month following LSG.…”
Section: Discussionsupporting
confidence: 68%
“…Surgical treatment of obesity has been shown to be affected in not only weight loss but also in the improvement of metabolic pro le. Following surgical treatment of obesity, decrease in the ongoing in ammatory process has been shown with various serum in ammatory markers, particularly CRP (13,4). LSG is one of the most effective bariatric surgery method in the treatment of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The results are related to sustained weight loss and the improvement or resolution of comorbidities associated with morbid obesity 5 , 29 . However, nutritional deficiencies stemming from food restriction associated with poor nutrient absorption are important issues to consider in the follow-up of these patients 6 , 16 , 19 , 25 .…”
Section: Introductionmentioning
confidence: 99%